2012
DOI: 10.2139/ssrn.972620
|View full text |Cite
|
Sign up to set email alerts
|

Short Selling and the Price Discovery Process

Abstract: We show that stock prices are more accurate when short sellers are more active. First, in a large panel of NYSE-listed stocks, intraday informational efficiency of prices improves with greater shorting flow. Second, at monthly and annual horizons, more shorting flow accelerates the incorporation of public information into prices. Third, greater shorting flow reduces post-earnings announcement drift for negative earnings surprises. Fourth, short sellers change their trading around extreme return events in a way… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(33 citation statements)
references
References 65 publications
3
30
0
Order By: Relevance
“…Negative information is subsequently incorporated into stock prices. The literature (e.g., Bris, Goetzmann, and Zhu, 2007;Boehmer, Jones, and Zhang, 2008;Boehmer and Wu 2013;Saffi and Sigurdsson, 2011) argues that short selling contributes to the market's informational efficiency -and our analyses confirm the existence of an explicit economic channel through which this contribution can be achieved.…”
Section: Implications For Information Disseminationsupporting
confidence: 75%
See 1 more Smart Citation
“…Negative information is subsequently incorporated into stock prices. The literature (e.g., Bris, Goetzmann, and Zhu, 2007;Boehmer, Jones, and Zhang, 2008;Boehmer and Wu 2013;Saffi and Sigurdsson, 2011) argues that short selling contributes to the market's informational efficiency -and our analyses confirm the existence of an explicit economic channel through which this contribution can be achieved.…”
Section: Implications For Information Disseminationsupporting
confidence: 75%
“…Moreover, although short selling is well recognized to increase the efficiency of the market (e.g., Bris, Goetzmann, and Zhu, 2007;Saffi and Sigurdsson, 2011), the channels through which it achieves such efficiency are less explored. One notable exception is Boehmer and Wu (2013), which illustrates how information gets incorporated into stock price through short sellers' intraday trading. Our unique contribution is to propose and test an explicit economic channel through which short selling can (indirectly) improve the price efficiency of the economy.…”
mentioning
confidence: 99%
“…The results are in accordance with the findings of , who detect negative effects by banning short selling on several equities during the financial crisis. Similar results are provided by Boehmer and Wu (2013). Hence, short sell bans lead to market inefficiency and damage market participants.…”
Section: Literature Review and Hypotheses Developmentsupporting
confidence: 73%
“…When compared to other US cross-listed stocks, Canadian stocks present several advantages: 1) the stocks are crosslisted in the US as ordinary shares rather than in the form of an American Depositary Receipt, which is a more complex intermediated facility; 2) the differences between the two trading venues in terms of the legal environment, accounting standards, and the degree of economic and financial market development are minimal; and 3) the stocks are traded concurrently on two markets sharing the same trading hours in the same time zone. 3 Previous research has found support for the model's theoretical predictions around earnings announcements(Reed, 2007;Boehmer and Wu, 2013) and in individual stocks' cross-autocorrelation with aggregate stock market returns(Bris, Goetzmann, and Zhu, 2007;Chen and Rhee, 2010;Saffi and Sigurdsson, 2011;Beber and Pagano, 2013;Boehmer and Wu, 2013). 3 Previous research has found support for the model's theoretical predictions around earnings announcements(Reed, 2007;Boehmer and Wu, 2013) and in individual stocks' cross-autocorrelation with aggregate stock market returns(Bris, Goetzmann, and Zhu, 2007;Chen and Rhee, 2010;Saffi and Sigurdsson, 2011;Beber and Pagano, 2013;Boehmer and Wu, 2013).…”
mentioning
confidence: 96%